Attending to Timely Contingencies: Promoting Physical Activity Uptake Among Adults with Serious Mental Illness with an Exercise-For-Mood vs. an Exercise-For-Fitness Prescription. Issue 2 (3rd April 2018) - Hearon, Bridget A.; Beard, Courtney; Kopeski, Lynne M.; Smits, Jasper A. J.; Otto, Michael W.; Björgvinsson, Thröstur
ABSTRACT: Despite evidence for both physical and mental health benefits achieved through regular exercise, most Americans fail to meet minimum recommendations. Altering the behavioral contingency from a focus on long-term health benefits to immediate mood benefits represents a novel method for exercise promotion. The current study examined a single-session exercise-for-mood intervention against two time-matched comparison conditions in 152 patients with serious mental illness attending a partial hospital program, a population marked by significant health disparities. This intervention was compared to a standard exercise-for-fitness intervention and a time-matched no-exercise control. Among patients with high levels of exercise prior to the partial hospital program, the exercise-for-mood intervention yielded significant increases in exercise. Implications for exercise promotion interventions among psychiatrically ill patients are discussed.